Particle history from massively parallel large eddy simulations of pulverised coal combustion in a large-scale laboratory furnace. (1st July 2020) - Rabaçal, Miriam; Costa, Mário; Rieth, Martin; Kempf, Andreas M
Highlights: Representation of fluid mixing and particle dispersion via massively parallel LES. Devolatilization kinetics optimized to fuel characteristics and heating conditions. Extension of previous study where the modelling framework was validated. Particle combustion process is highly affected by its trajectory. Abstract: A study on the coal particle history during combustion in a large-scale furnace using large eddy simulation is presented. The massively parallel execution produces a high-resolution representation of the fluid mixing and particle dispersion throughout the whole computational domain. The coal combustion is modelled using well-established, cost-effective combustion models. A specific feature of the devolatilization model is the optimisation of the kinetic constants for the furnace operating condition, which were obtained through an iterative procedure between particle heating rates from full large eddy simulation runs and the advanced model Chemical Percolation Devolatilization. In a previous work, we showed that the classical coal combustion models, when used in a high-resolution massively parallel large eddy simulation, lead to satisfactory predictions of the in-flame gas properties, namely gas temperature and gas species concentrations. In this work, we went beyond the comparisons between gas phase measurements and predictions. Single particles were tracked over time and instantaneous ensambles were collected to obtain a better understanding of the conditions that coal particles are subjected to in the investigated test case. The particles trajectory, combustion history and instantaneous state distribution were analysed. The volatile flame features were related with the characteristic trajectory of different sized particles. The combustion history revealed that particles are subjected to large variations of heating rates, including very short sequential periods alternating between heating and cooling during the early stages of combustion, due to the high turbulence intensity in the near burner region. Finally, the state distribution of the ensamble provided a global picture of the instantaneous coal combustion process.